Metode Fuzzy Sugeno untuk Penilaian Kinerja Guru SMK Tamansiswa 3 Jakarta - Fanisya Alva Mustika (Universitas Indraprasta PGRI Jakarta, 2021)
Determine model teacher or teachers who performed well is one effort in improving on teacher performance.The problem in smk tamansiswa 3 jakarta is no fixed on the performance assessment teachers. Thus there needs the assessment system on teacher performance that can help in determining teachers with management best performance helped build management for providing advice for teachers based on the total score earned by. This system made by using fuzzy logic sugeno.Criteria that are applied in this system readiness matter, among others: learning, media uses, objective, curriculum development, their mastery of the material, the presence of, class control, ability motivate students, ability create a class pleasing. Criteria divided into the fuzzy good , enough and bad .The result of this research was the assessment system uses the teacher performance with the accuracy of fuzzy sugeno 98,92 % .